Who is afraid of post-growth?. (30th June 2021) - Cojanu, Valentin
The present times when economic activity has been drastically reduced and people's pressure on the environment has receded provide us with a rare economic experiment of thinking beyond growth. The post-growth message cuts across diverse anti-establishment movements, but essentially all identify themselves with the goal of controlling growth to the end of preserving the good life between us and future people. We advance reasons to rethink our relationships towards: 1) the economic role of the common good: how would economic science look like if it were concerned with good life rather than growth?; 2) the exercise of power: how can we constructively manage relations with those who provide access to (economic) resources?; 3) the moral reason for change beyond growth.